USING ESL PODCAST TO IMPROVE STUDENTS LISTENING COMPREHENSION: A CASE STUDY OF THE ELEVENTH GRADE - Salsabella Noviyanto Putri; Laily Nur Affini; Sri Wahyuni (STKIP Subang, 2023)
ABSTRACT Listening comprehension is one of the understandings that requires high understanding and repetition to understand the topic being heard. However, it is rarely reviewed in schools because, in its implementation, schools must have adequate facilities. The purpose of this study is to determine students' listening comprehension before and after treatment using ESL podcasts by Jeff McQuillan to determine whether or not the use of ESL podcasts effectively improves listening comprehension. This quantitative research method used one group of pre-test and post-test samples (34 students) in eleventh-grade SMA Kesatrian 1 Semarang. To test the effectiveness or ineffectiveness of podcasts, researchers used the t-test. As secondary data, there was an open questionnaire regarding supporting and inhibiting factors in listening learning. The results showed that ESL podcasts were effective in improving listening comprehension. This was obtained from the pre-test (M = 42.3529) and post-test (M = 75.0000) with Sig. (2-tailed) ,000 <0.05 based on the t-test decision-making shows significance if < 0.05.Moreover, the results of the questionnaire, 27 students felt that their listening comprehension had improved, and seven students felt an increase in listening comprehension. The highest factor supporting listening learning is focus, and the highest inhibiting factor is the lack of vocabulary. Keywords: ESL Podcast, Listening Comprehension, English Learning